2018
DOI: 10.1103/physrevapplied.9.014004
|View full text |Cite
|
Sign up to set email alerts
|

Multiharmonic Frequency-Chirped Transducers for Surface-Acoustic-Wave Optomechanics

Abstract: Wide passband interdigital transducers are employed to establish a stable phase-lock between a train of laser pulses emitted by a mode-locked laser and a surface acoustic wave generated electrically by the transducer. The transducer design is based on a multi-harmonic split-finger architecture for the excitation of a fundamental surface acoustic wave and a discrete number of its overtones. Simply by introducing a variation of the transducer's periodicity a frequency chirp is added. This combination results in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…First examples where phonons coupled to semiconductor quantum dots improve application relevant properties include the here discussed phonon-assisted state preparation [23,[25][26][27]218], the establishment of off-resonant QD-cavity couplings [28][29][30][31][32][33][34][35][36], the phonon mediated brightness enhancement of dots detuned from an embedding cavity [260], the possibility to enhance the photon purity with excitations spectrally separated from the excitation [288], a high cavity-photon feeding efficiency that is robust against variations of the driving frequency [37] as well as the possibility to trigger simultaneous photon emission from remote quantum dots with different transitions frequencies [218]. Further applications comprise lasing manipulated by phonon pulses [289][290][291], position sensing using phonon shifts [292] or modulations of quantum dots via surface acoustic waves [293][294][295][296]. In view of these developments future devices can be expected to benefit from phonons rather than being limited in their functionality.…”
Section: Discussionmentioning
confidence: 99%
“…First examples where phonons coupled to semiconductor quantum dots improve application relevant properties include the here discussed phonon-assisted state preparation [23,[25][26][27]218], the establishment of off-resonant QD-cavity couplings [28][29][30][31][32][33][34][35][36], the phonon mediated brightness enhancement of dots detuned from an embedding cavity [260], the possibility to enhance the photon purity with excitations spectrally separated from the excitation [288], a high cavity-photon feeding efficiency that is robust against variations of the driving frequency [37] as well as the possibility to trigger simultaneous photon emission from remote quantum dots with different transitions frequencies [218]. Further applications comprise lasing manipulated by phonon pulses [289][290][291], position sensing using phonon shifts [292] or modulations of quantum dots via surface acoustic waves [293][294][295][296]. In view of these developments future devices can be expected to benefit from phonons rather than being limited in their functionality.…”
Section: Discussionmentioning
confidence: 99%
“…First, multi‐passband IDTs were fabricated in a standard lift‐off process using a Cr/Au (5 nm/50 nm) metallization which is inert to hydrofluoric acid (HF) etching employed to release the nanophononic strings.…”
Section: Methodsmentioning
confidence: 99%
“…Most strikingly, the broadening observed for the QD inside the nanophononic string is largely enhanced compared to the QD in the unpatterned region. The observed broadening can be described by a Lorentzian line modulated in time with a frequency fRF. It is given by truerightI()E=leftI0+fRF2Aπleft×0.16em01/fRFw4·()E()E0+normalΔE0.16em·0.16emsin()2π0.16em·0.16emfRF0.16em·0.16emt2+w2dt,in which ΔE and w denote the amplitude of the optomechanical modulation and the unperturbed linewidth of the QD emission line, respectively. Best fits of Equation (full lines in Figure b,c) faithfully reproduce the experimental data and allow us to quantify ΔE to be 0.23 and 1.40 meV for the Rayleigh SAW and on the nanophononic string, respectively.…”
mentioning
confidence: 99%
“…[ 70 ] While in the introduced geometry only a single SAW frequency can be launched, new developments use more sophisticated finger patterns of the IDT that allow to tune the SAW frequency between a few hundred MHz and a few GHz in a single device. [ 71 ] To reach smaller frequencies, one can follow a wave mixing approach and reach frequencies below the Hz range by difference frequency generation of slightly detuned SAWs. [ 72 ] Reviews that treat the current status and future perspectives of SAWs can be found in refs.…”
Section: Generation Of Coherent Phononsmentioning
confidence: 99%
“…a) Schematic picture of the sample structure. Reproduced under the terms of a Creative Commons Attribution 4.0 License (CC-BY) [71]. Copyright 2018, The Authors, published by the American Physical Society.…”
mentioning
confidence: 99%